Machine Learning Approach for Marketing Intelligence: Managerial Application (International Journal of Engineering and Computer Science, 2017)
Marketing Intelligent Approach is a cutting edge for marketing management support system to deal with knowledge by machine learning and other soft computing techniques. The range of potential applications of machine learning techniques in marketing management are consumer behavior, optimization of productmarket structure, managing the market mix, strategic marketing, finance domain etc describes the synergy between marketing and intelligent systems, specially machine learning techniques. Interactive promotion is a matching field for marketing; where intelligent systems can be applied. The above description suggests us that marketing is a multifaceted field of decision making. Marketing decision is a combination of judgments and analysis which involves a huge degree of intuition in which knowledge and expertise are required to take decision, therefore here Artificial Intelligence (AI) can play an important role. Machine learning is an AI component that observes historic data of actions and does experiential learning by putting the knowledge to use to perform similar process in new computational settings1 . This paper describes about the potential benefits associated with the application of machine learning techniques to the field of marketing management. It also describes the fundamental techniques and introduces relevant marketing fields to which machine learning approach such as Data Mining, AI, and Soft Computing techniques could be applied.